Lithium secondary battery and its manufacturing method

JP7640174B2Active Publication Date: 2025-03-05LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023529103
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2022-03-28
Publication Date
2025-03-05
Estimated Expiration
2042-03-28

AI Technical Summary

Benefits of technology

【0009】 本発明に係るリチウム二次電池は、有機電解質溶媒を使用した場合よりも発火点の高い共融混合物を使用することにより、安定性が向上する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640174000001
    Figure 0007640174000001
  • Figure 0007640174000002
    Figure 0007640174000002
  • Figure 0007640174000003
    Figure 0007640174000003
Patent Text Reader

Abstract

In order to achieve the object of the present invention, the present invention relates to a lithium secondary battery including a positive electrode, a separator, and a negative electrode, and filled with an electrolyte solution containing a eutectic mixture of succinonitrile and a lithium salt as a solvent, and a method for manufacturing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0041444, filed on March 30, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a method for producing a lithium secondary battery comprising an electrolyte solution comprising succinonitrile as a solvent and a eutectic mixture of a lithium salt. [Background technology]

[0003] Recently, the application areas of lithium secondary batteries have been rapidly expanded from power supply for electronic devices such as electrical, electronic, communication, and computer equipment to power storage supply for large-area devices such as automobiles and power storage devices, and thus there is an increasing demand for lithium secondary batteries that have high capacity, high output, and high stability.

[0004] A lithium secondary battery is generally manufactured by preparing a positive electrode including a positive electrode active material such as a lithium-containing transition metal oxide and a negative electrode including a carbon material and / or a silicon material negative electrode active material capable of absorbing and releasing lithium ions, laminating the positive electrode and the negative electrode on both sides of a separator to form an electrode assembly of a predetermined shape, and then inserting the electrode assembly and an electrolyte into a battery case. In this case, it is generally known to use a non-aqueous electrolyte in which a lithium salt is dissolved in a carbonate-based organic solvent such as ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), etc. as the electrolyte. However, the carbonate-based organic solvent has a disadvantage that it is highly likely to volatilize and is low in safety due to combustion caused by an increase in the temperature of the surrounding temperature and the battery itself. Therefore, attempts have been made to develop an electrolyte for lithium secondary batteries that can compensate for such disadvantages, and among them, there is an attempt to use a eutectic mixture as the electrolyte for lithium secondary batteries. A eutectic mixture is a mixture of solid substances that exists in a liquid state in a specific eutectic temperature range, and has a higher ignition point and higher high temperature stability than conventional carbonate-based organic solvents.

[0005] However, when a eutectic mixture is used as an electrolyte, there is a problem that the performance of the lithium secondary battery is deteriorated due to low lithium ion conductivity. Summary of the Invention [Problem to be solved by the invention]

[0006] In order to solve the above problems, the present invention aims to provide a lithium secondary battery and a manufacturing method thereof, which can ensure both performance and safety for a lithium secondary battery injected with an electrolyte solution using a eutectic mixture having excellent safety as a solvent. [Means for solving the problem]

[0007] In order to achieve the above object, the present invention provides a lithium secondary battery comprising a positive electrode, a separator, and a negative electrode, and an electrolyte solution containing a eutectic mixture of succinonitrile and a lithium salt as a solvent.

[0008] In addition, in order to achieve the above object, the present invention is characterized in that a new activation (formation) process is applied to a lithium secondary battery injected with an electrolyte solution containing a eutectic mixture of succinonitrile and a lithium salt as a solvent, the lithium secondary battery being charged until the remaining capacity (SOC) is 55 to 65%. Effect of the Invention

[0009] The lithium secondary battery according to the present invention has improved stability due to the use of a eutectic mixture which has a higher ignition point than when an organic electrolyte solvent is used.

[0010] In addition, a new activation step is applied to the lithium secondary battery manufactured by the method for manufacturing a lithium secondary battery according to the present invention, and a large amount of gas is generated by activation. The method for manufacturing a lithium secondary battery according to the present invention suppresses the swelling phenomenon of the battery by removing a large amount of gas generated in the activation step in a degassing step, and has excellent battery characteristics such as initial capacity and cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The terms and words used in this specification and the claims should not be interpreted limited to their ordinary and dictionary meanings, but should be interpreted in a way that is consistent with the technical ideas of the present invention, based on the principle that the inventor himself / herself can appropriately define the concepts of terms in order to explain the invention in the best possible way.

[0012] In this specification, terms such as "comprise", "comprise", or "have" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.

[0013] The present invention will now be described in more detail.

[0014] First, a method for producing a lithium secondary battery of the present invention will be described.

[0015] A method for manufacturing a lithium secondary battery according to the present invention may include a step of preparing a lithium secondary battery including a positive electrode, a separator, and a negative electrode, and injecting an electrolyte solution including a eutectic mixture of succinonitrile and a lithium salt; an activation step including a process of charging the lithium secondary battery until a state of charge (SOC) is 55 to 65%; and a degassing step.

[0016] electrolyte (A) Eutectic mixture The electrolyte injected into the lithium secondary battery according to the present invention may include a eutectic mixture of succinonitrile and a lithium salt as a solvent. The eutectic mixture of succinonitrile and a lithium salt means a mixture of solid succinonitrile and solid lithium salt that exists in a liquid state in a specific eutectic temperature range. The eutectic mixture of succinonitrile and a lithium salt has a higher ignition point than conventional organic electrolyte solvents, and when used as an electrolyte, the high temperature stability is improved.

[0017] The eutectic temperature of the eutectic mixture of succinonitrile and lithium salt according to the present invention may be 20 to 30° C., specifically 23 to 27° C. Only when a eutectic mixture having such a eutectic temperature is used can it exist in a liquid state at room temperature and can be injected into a secondary battery as an electrolyte.

[0018] Meanwhile, the electrolyte may contain a eutectic mixture of succinonitrile and a lithium salt in an amount of 80% by weight or more, preferably 80 to 95% by weight or more, and more preferably 85 to 90% by weight or more, based on the total weight of the electrolyte. When the eutectic mixture of succinonitrile and a lithium salt is used in the above amount as a solvent contained in the electrolyte, a lithium secondary battery having excellent high temperature stability can be obtained.

[0019] The eutectic mixture of succinonitrile and a lithium salt according to the present invention may be a eutectic mixture of succinonitrile and a lithium salt, for example, a eutectic mixture of succinonitrile and lithium bis(fluorosulfonyl)imide (LiFSI).

[0020] In this case, the eutectic mixture may contain 0.5 to 1.5 mol, preferably 0.7 to 1.3 mol, of lithium bis(fluorosulfonyl)imide (LiFSI) per 1 L of succinonitrile. When the above range is satisfied, the mobility of lithium ions is ensured, and the ion conductivity that allows sufficient capacity characteristics to be expressed can be obtained.

[0021] The eutectic mixture according to the present invention may contain succinonitrile, lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluoro(oxalato)borate (LiODFB). When the eutectic mixture contains lithium difluoro(oxalato)borate (LiODFB), a protective layer is formed on the positive electrode current collector by BF bonding, thereby suppressing corrosion of the positive electrode current collector, for example, an aluminum thin film.

[0022] The eutectic mixture may contain 0.3 to 0.5 mol, preferably 0.35 to 0.45 mol, of lithium difluoro(oxalate)borate (LiODFB) per L of succinonitrile. When the above range is satisfied, corrosion of the positive electrode current collector, for example, an aluminum thin film, can be effectively suppressed.

[0023] In the eutectic mixture according to the present invention, the molar ratio of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium difluoro(oxalate)borate (LiODFB) may be 8:5 to 10:3, preferably 8.5:4.5 to 9.5:3.5. When the molar ratio of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium difluoro(oxalate)borate (LiODFB) in the eutectic mixture satisfies the above range, it is possible to obtain an effect of suppressing corrosion of the positive electrode current collector while obtaining excellent lithium ion conductivity.

[0024] (B) Additives The electrolyte injected into the lithium secondary battery according to the present invention may further include an additive in the eutectic mixture solvent to prevent electrolyte decomposition, improve low-temperature high-rate discharge characteristics, high-temperature stability, prevent overcharging, suppress battery expansion at high temperatures, etc. Examples of such other additives include at least one selected from the group consisting of halogen-substituted or unsubstituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based or phosphite-based compounds, nitrile-based compounds, benzene-based compounds, amine-based compounds, and silane-based compounds.

[0025] Examples of the halogen-substituted or unsubstituted carbonate-based compound include vinylene carbonate (VC), vinylethylene carbonate, and fluoroethylene carbonate (FEC).

[0026] The sultone-based compound may be, for example, at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.

[0027] The sulfate-based compound may be, for example, ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyl trimethylene sulfate (MTMS).

[0028] The phosphate- or phosphite-based compound may be, for example, one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite.

[0029] The nitrile compound may be, for example, at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.

[0030] The benzene-based compound may be fluorobenzene, the amine-based compound may be triethanolamine or ethylenediamine, and the silane-based compound may be tetravinylsilane.

[0031] Among these additives, the addition of a halogen-substituted or unsubstituted carbonate-based compound can form a stronger anode protective film on the anode surface during the initial activation process of the secondary battery. The halogen-substituted or unsubstituted carbonate-based compound may include at least one selected from the group consisting of vinylene carbonate (VC) and fluoroethylene carbonate (FEC).

[0032] Preferably, the electrolyte according to the present invention may contain vinylene carbonate (VC) as an additive, in which case there is an advantage that a negative electrode protective film is formed and battery performance is improved.

[0033] The vinylene carbonate (VC) may be contained in an amount of 1 to 5% by weight, preferably 2 to 4% by weight, based on the total weight of the electrolyte solution. When the amount is within the above range, a negative electrode protective film is formed, which has the effect of improving the battery life.

[0034] Preferably, the electrolyte of the present invention may contain a fluoroethylene carbonate (FEC) additive, which forms a LiF layer to aid in the formation of the SEI, reduce the crystallinity of succinonitrile, and inhibit the polymerization of succinonitrile.

[0035] The fluoroethylene carbonate (FEC) additive may be included in an amount of 3 to 15 wt %, preferably 5 to 15 wt %, based on the total weight of the electrolyte solution, which can reduce the crystallinity of succinonitrile and effectively inhibit polymerization of succinonitrile.

[0036] Preparation for lithium secondary batteries The lithium secondary battery according to the present invention may be prepared in the form of a lithium secondary battery including a positive electrode, a separator, and a negative electrode, and filled with an electrolyte solution including a eutectic mixture of succinonitrile and a lithium salt. The electrolyte solution has been described above, so a description thereof will be omitted, and the other components will be described below.

[0037] The lithium secondary battery of the present invention may be manufactured by a conventional method known in the art, for example, by forming an electrode assembly in which a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode are sequentially stacked, inserting the electrode assembly into a battery case, and injecting the electrolyte according to the present invention into the battery case.

[0038] (a) Positive electrode The positive electrode may be prepared by coating a positive electrode current collector with a positive electrode mixture slurry including a positive electrode active material, a binder, a conductive material, and a solvent.

[0039] The positive electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like may be used.

[0040] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, including LCO (LiCoO2), LNO (LiNiO2), LMO (LiMnO2), LiMn2O4, LiCoPO4, LFP (LiFePO4), LiNiMnCoO2, and NMC (LiNiCoMnO2), etc., such as LiNi 1-x-y-z Co x M 1 y M 2 z O2 (where M 1 and M 2 are each independently selected from the group consisting of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg, and Mo, and x, y, and z are each independently 0 ≦ x < 0.5, 0 ≦ y < 0.5, 0 ≦ z < 0.5, x + y + z = 1 as the atomic fraction of the oxide composition elements) and may be one or more selected therefrom.

[0041] Specifically, it may include a lithium metal oxide containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium.

[0042] More specifically, the lithium metal oxide is a lithium-manganese-based oxide such as LiMnO2, LiMn2O4; a lithium-cobalt-based oxide such as LiCoO2; a lithium-nickel-based oxide such as LiNiO2; LiNi 1-Y Mn Y O2 (0 < Y < 1), LiMn 2-z Ni z O4 (0 < Z < 2), etc., lithium-nickel-manganese-based oxides; LiNi 1-Y1 Co Y1 O2 (0 < Y1 < 1), etc., lithium-nickel-cobalt-based oxides; LiCo 1-Y2 Mn Y2 O2 (0 < Y2 < 1), LiMn 2-z1 Co z1 O4 (0 < Z1 < 2), etc., lithium-manganese-cobalt-based oxides; Li(Ni p Co q Mn r1)O2 (0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1), Li(Ni p1 Co q1 Mn r2 )O4 (0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), etc. lithium-nickel-manganese-cobalt oxides; and Li(Ni p2 Co q2 Mn r3 M S2 )O2 (M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are, as atomic fractions of independent elements, 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, p2 + q2 + r3 + s2 = 1), etc., may be one or more selected from lithium-nickel-cobalt-transition metal (M) oxides.

[0043] Among these, in terms of being able to enhance the capacity characteristics and stability of the battery, the lithium metal oxide is LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (for example, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.); or lithium nickel cobalt aluminum oxide (for example, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), and considering the remarkable improvement effect by controlling the types and content ratios of the constituent elements forming the lithium composite metal oxide, the lithium composite metal oxide is Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2.

[0044] The positive electrode active material may be contained in the positive electrode mixture slurry in an amount of 60% to 99% by weight, preferably 70% to 99% by weight, and more preferably 80% to 98% by weight, based on the total weight of solids excluding the solvent.

[0045] The binder is a component that assists in binding the active material and conductive material to the current collector.

[0046] Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof.

[0047] Typically, the binder may be contained in the positive electrode mixture slurry in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent.

[0048] The conductive material is a component for further improving the conductivity of the positive electrode active material.

[0049] The conductive material is not particularly limited as long as it is conductive and does not induce a chemical change in the battery. For example, graphite; carbon-based substances such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used.

[0050] Typically, the conductive material may be contained in the positive electrode mixture slurry in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent.

[0051] The solvent may include an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a preferred viscosity when the positive electrode active material and, optionally, the binder and conductive material are included. For example, the solvent may be included so that the concentration of the solid content including the positive electrode active material and, optionally, the binder and conductive material is 50% by weight to 95% by weight, preferably 50% by weight to 80% by weight, and more preferably 55% by weight to 70% by weight.

[0052] (b) Negative electrode The negative electrode may be manufactured by coating a negative electrode current collector with a negative electrode slurry including a negative electrode active material, a binder, a conductive material, and a solvent, followed by drying and rolling.

[0053] The negative electrode current collector generally has a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, copper; stainless steel; aluminum; nickel; titanium; calcined carbon; copper or stainless steel surface treated with carbon, nickel, titanium, silver, or the like; or an aluminum-cadmium alloy. In addition, like the positive electrode current collector, fine irregularities may be formed on the surface to strengthen the binding force of the negative electrode active material, and may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0054] In addition, the negative electrode active material may include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal, or an alloy of these metals and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.

[0055] The carbonaceous material capable of reversibly intercalating / deintercalating lithium ions may be any carbonaceous negative electrode active material commonly used in lithium ion lithium secondary batteries, and representative examples thereof include crystalline carbon, amorphous carbon, or a combination of both. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, calcined coke, etc.

[0056] As the metal or the alloy of these metals and lithium, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn, or an alloy of these metals and lithium may be used.

[0057] Examples of the metal composite oxide include PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1) and Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8), one or more selected from the group consisting of may be used.

[0058] Examples of the substance capable of doping and undoping lithium include Si, SiO x (0 < x ≦ 2), Si - Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn, SnO2, Sn - Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Sn), etc. Also, at least one of these may be mixed with SiO2 and used. The element Y may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db (dubnium), Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0059] Examples of the transition metal oxide include lithium - containing titanium composite oxide (LTO), vanadium oxide, lithium vanadium oxide, etc.

[0060] In the present invention, the negative electrode active material is preferably graphite.

[0061] The negative electrode active material may be contained in the negative electrode mixture slurry in an amount of 60% to 99% by weight, preferably 70% to 99% by weight, and more preferably 80% to 98% by weight, based on the total weight of solids excluding the solvent.

[0062] The binder is a component that helps to bond the conductive material, active material, and current collector together. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof.

[0063] Typically, the binder may be contained in the negative electrode mixture slurry in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent.

[0064] The conductive material is a component for further improving the conductivity of the negative electrode active material. Such a conductive material is not particularly limited as long as it is conductive without inducing chemical changes in the battery, and may be, for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fiber such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, or nickel powder; conductive whisker such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0065] The conductive material may be contained in the negative electrode mixture slurry in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent.

[0066] The solvent may include water; or an organic solvent such as NMP (N-methyl-2-pyrrolidone), alcohol, etc., and may be used in an amount that provides a preferred viscosity when the negative electrode active material and, optionally, a binder and a conductive material are included. For example, the solvent may be included so that the concentration of solids including the negative electrode active material and, optionally, a binder and a conductive material is 50% by weight to 95% by weight, preferably 70% by weight to 90% by weight.

[0067] When a metal is used as the negative electrode, the negative electrode may be manufactured by physically bonding, rolling, or depositing a metal on a metal thin film or the negative electrode current collector. The deposition method may be an electrochemical deposition method or a chemical vapor deposition method.

[0068] For example, the metal thin film itself or the metal bonded / rolled / deposited onto the negative electrode current collector may include one metal or an alloy of two metals selected from the group consisting of nickel (Ni), tin (Sn), copper (Cu) and indium (In).

[0069] (c) Separation membrane The lithium secondary battery according to the present invention may include a separator between the positive electrode and the negative electrode.

[0070] The separator serves to block an internal short circuit between the two electrodes and to impregnate the electrolyte. A polymer resin, a filler, and a solvent may be mixed to prepare a separator composition, and the separator composition may be directly coated on the upper surface of an electrode and dried to form a separator film, or the separator composition may be cast on a support, dried, and the separator film may be peeled off from the support and laminated on the upper surface of an electrode to form a separator film.

[0071] The separator may be a commonly used porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in combination; a commonly used porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or a safety-reinforcing separator (SRS) separator having an organic / inorganic composite coating layer applied to both sides of a porous film substrate, but is not limited thereto.

[0072] In this case, the pore diameter of the porous separation membrane may be generally 0.01 μm to 50 μm, the porosity may be generally 5% to 95%, and the thickness of the porous separation membrane may be generally in the range of 5 μm to 300 μm.

[0073] Activation Phase The method for manufacturing a lithium secondary battery according to the present invention may include an activation (formation) step including a process of charging the above-mentioned lithium secondary battery until the state of charge (SOC) is 55 to 65%.

[0074] The activation stage is a stage in which a coating layer of the SEI (Solid electrolyte interface) of the negative electrode is formed. In the conventional activation stage, the battery was generally charged to a state of charge (SOC) in the range of 10% to 40%.

[0075] However, the activation step of the present invention may generate a larger amount of gas than the conventional activation step by charging until the state of charge (SOC) is 55 to 65%. The method for manufacturing a lithium secondary battery according to the present invention can suppress the swelling phenomenon of the battery by removing a large amount of gas generated in the activation step in the degassing step described below, and can also have an excellent effect on battery characteristics such as initial capacity and cycle characteristics.

[0076] The activation step according to the present invention comprises: 4.5 hours to 7.5 hours, or The charging may be performed for 4 to 7 hours, preferably 5.5 to 6.5 hours. In the activation step according to the present invention, by charging for a time period within the above range, a large amount of gas can be sufficiently generated in the activation step.

[0077] The activation step according to the present invention may be carried out at 40-50°C.

[0078] The charging conditions in the activation step, except for the state of charge (SOC), charging time and charging temperature, may be determined according to methods known in the art. Specifically, charging is performed at a charging voltage of 3.6 to 3.65 V, and at a pressure of 0.5 to 5 kgf / cm. 2 However, the charging voltage and pressure may vary depending on the type and characteristics of the lithium secondary battery, and are not limited thereto.

[0079] Degassing stage The method for manufacturing a lithium secondary battery according to the present invention may include a step of degassing the lithium secondary battery that has been subjected to the activation step.

[0080] The degassing process is for removing activation gas generated inside the secondary battery through the activation step.

[0081] In this deaeration step, various deaeration techniques known at the time of filing of the present invention may be used. For example, in a pouch-type secondary battery having one side extended, the deaeration step may be performed by cutting the extended portion, removing gas by placing the surrounding area in a vacuum state at a certain temperature, and then sealing the cut portion. However, since such deaeration techniques are widely known to those skilled in the art, detailed description thereof will be omitted.

[0082] The lithium secondary battery according to the present invention manufactured by the above-mentioned method is not only excellent in safety since a eutectic mixture having a high ignition point is used as a solvent for the electrolyte, but also has excellent initial capacity characteristics, life characteristics and swelling characteristics since an activation process is performed under specific conditions.

[0083] Specifically, the lithium secondary battery according to the present invention includes a positive electrode, a separator, a negative electrode, and an electrolyte, and the electrolyte includes a eutectic mixture of succinonitrile and a lithium salt in an amount of 80% by weight or more based on the total weight of the electrolyte. The configurations of the positive electrode, separator, negative electrode, and electrolyte are as described above, so a detailed description will be omitted.

[0084] On the other hand, the lithium secondary battery according to the present invention has a discharge capacity retention rate of 80% or more, preferably 85% or more, after 79 cycles when repeatedly charged and discharged at a constant current of 0.1 C in the range of 2.5 V to 4.25 V, and has excellent life characteristics.

[0085] Furthermore, the lithium secondary battery according to the present invention has a cell volume increase rate of 10% or less, preferably 6% or less, measured after storage at 60° C. for two weeks, and has excellent swelling properties.

[0086] The lithium secondary battery according to the present invention may have a discharge capacity retention rate of 80% or more, preferably 85% or more, after 79 cycles when repeatedly charged and discharged at a constant current of 0.1 C in the range of 2.5 V to 4.25 V.

[0087] The lithium secondary battery according to the present invention can be effectively used in portable devices such as mobile phones, notebook computers, and digital cameras; and electric vehicles such as hybrid electric vehicles (HEVs).

[0088] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0089] The battery module or battery pack may be used as a power source for one or more medium to large devices including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); and power storage systems.

[0090] The shape of the lithium secondary battery of the present invention is not particularly limited, but may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0091] The lithium secondary battery according to the present invention can be used as a battery cell used as a power source for small devices, and can also be preferably used as a unit battery for medium- to large-sized battery modules including a large number of battery cells.

[0092] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.

[0093] Manufacturing Example 1 Lithium bisfluorosulfonylimide (LiFSI) and lithium difluoro(oxalate)borate (LiODFB) were dissolved in 1 L of succinonitrile at 0.9 mol and 0.4 mol, respectively, to prepare a eutectic mixture of succinonitrile and lithium salt. Vinylene carbonate (VC) and fluoroethylene carbonate (FEC) were added as additives at 3 and 10 wt %, respectively, based on the total weight of the electrolyte to prepare an electrolyte.

[0094] Manufacturing Example 2 Ethylene carbonate (EC): diethyl carbonate (DEC): succinonitrile: fluoroethylene carbonate (FEC) were added in a volume ratio of 21:49:20:10, and lithium bisfluorosulfonylimide (LiFSI) was dissolved therein to a molar concentration of 1.2 M to prepare an electrolyte.

[0095] Example 1 LiNi as the positive electrode active material 0.8 Mn 0.1 Co 0.1 A positive electrode slurry (solid content: 50 wt%) was prepared by mixing 97.5 wt% O2, 1.0 wt% carbon black as a conductive material, and 1.5 wt% polyvinylidene fluoride as a binder in N-methyl-2-pyrrolidone solvent. The positive electrode slurry was applied to one side of a 12 μm-thick aluminum thin film, dried, and then rolled to prepare a positive electrode.

[0096] Anode slurry (solid content: 60 wt%) was prepared by mixing 95.0 wt% graphite as anode active material, 1.5 wt% carbon black as conductive material, and 3.5 wt% SBR-CMC (butadiene rubber-carboxymethyl cellulose) as binder in deionized water. The anode slurry was applied to both sides of a copper foil with a thickness of 6 μm, dried, and then rolled to prepare anode.

[0097] Two single-sided positive electrodes and one double-sided negative electrode were sequentially stacked between four polyolefin-based porous separators coated with aluminum oxide inorganic particles to prepare a monocell-type electrode assembly, which was then placed inside a pouch-type battery case and the electrolyte prepared in Preparation Example 1 was injected to assemble a lithium secondary battery.

[0098] The assembled lithium secondary battery was activated by charging at 45° C. with a charging voltage of 3.65 V and a constant current of 0.1 C for 6 hours until the state of charge (SOC) reached 60%. The activated lithium secondary battery was then degassed.

[0099] Comparative Example 1 A lithium secondary battery was produced in the same manner as in Example 1, except that the electrolyte solution of Production Example 2 was used instead of the electrolyte solution of Production Example 1.

[0100] Comparative Example 2 A lithium secondary battery was manufactured in the same manner as in Example 1, except that in the activation step, charging was performed until the state of charge (SOC) reached 30% for 3 hours.

[0101] Comparative Example 3 A lithium secondary battery was manufactured in the same manner as in Example 1, except that in the activation step, charging was performed until the 5-hour state of charge (SOC) reached 50%.

[0102] Comparative Example 4 A lithium secondary battery was manufactured in the same manner as in Example 1, except that in the activation step, charging was performed until the 7-hour remaining capacity (SOC) reached 70%.

[0103] Experimental Example 1: Evaluation of initial discharge capacity The lithium secondary batteries prepared in Example 1 and Comparative Examples 1 to 4 were each charged to 4.2 V at 25° C. at a constant current of 0.1 C, and then discharged to 2.5 V at a constant current of 0.1 C to measure the initial discharge capacity. At this time, a charger / discharger PNE-0306 from PNE solution was used. The measurement results are shown in Table 1 below.

[0104] [Table 1]

[0105] It was confirmed that Example 1, in which an electrolyte solution containing a eutectic mixture of succinonitrile and lithium salt as a solvent was injected, had a larger initial discharge capacity than Comparative Example 1, in which a conventional organic electrolyte solvent was used. In particular, Comparative Example 1, in which succinonitrile was added as an additive to an organic solvent used in a conventional electrolyte, showed a significant decrease in initial discharge capacity, and the battery was disassembled and analyzed, and corrosion of the Al current collector was observed.

[0106] Meanwhile, in the case of Example 1, in which the activation step was performed by charging until the state of charge (SOC) reached 60%, it was confirmed that the initial discharge capacity was larger than that of Comparative Examples 2 to 4, in which the state of charge (SOC) was charged until the state of charge reached 30%, 50%, and 70%.

[0107] Experimental Example 2: Evaluation of cycle characteristics Each of the batteries manufactured in Example 1 and Comparative Examples 2 to 4 was charged at room temperature (25° C.) at a constant current of 0.1 C to 4.2 V and discharged at a constant current of 0.1 C to 2.5 V as one cycle, and then the capacity retention rate relative to the initial capacity after 79 cycles was measured. The results are shown in Table 2 below.

[0108] [Table 2]

[0109] In the case of Example 1, in which the activation step of charging until the state of charge (SOC) reached 60% was performed, it was confirmed that the cycle characteristics were superior to those of Comparative Examples 2 to 4, in which the state of charge (SOC) was charged until the state of charge reached 30%, 50%, and 70%.

[0110] Experimental Example 3 - Evaluation of swelling The secondary batteries prepared in Example 1 and Comparative Examples 1 to 4 were each fully charged to 4.2 V and then stored at 60° C. for two weeks.

[0111] Before storage, the cell volume of the fully charged secondary battery was measured and set as the initial secondary battery volume.

[0112] After two weeks, the cell volume of the secondary battery was measured to calculate the volume that had swelled during the two-week storage period. The percentage of the increased cell volume relative to the initial cell volume of the secondary battery was calculated to derive the cell volume increase rate after two weeks. The results are shown in Table 3 below.

[0113] [Table 3]

[0114] In the case of Example 1, in which an electrolyte solution containing a eutectic mixture of succinonitrile and a lithium salt was injected as a solvent, it was confirmed that swelling was less than that in Comparative Example 1, in which a conventional organic electrolyte solvent was used. Also, in the case of Example 1, in which an activation step of charging until the state of charge (SOC) reached 60% was performed, it was confirmed that swelling was less than that in Comparative Examples 2 to 4, in which charging until the state of charge (SOC) reached 30%, 50%, and 70%.

Claims

1. providing a lithium secondary battery including a positive electrode, a separator, and a negative electrode; and filling the battery with an electrolyte including a eutectic mixture of succinonitrile and a lithium salt as a solvent; an activation step including charging the lithium secondary battery until the remaining capacity (SOC) is 55-65%; and degassing the battery.

2. 2. The method for producing a lithium secondary battery according to claim 1, wherein the eutectic mixture of succinonitrile and a lithium salt is contained in an amount of 80% by weight or more based on the total weight of the electrolyte.

3. 3. The method for producing a lithium secondary battery according to claim 1, wherein the eutectic temperature of the eutectic mixture is 20 to 30° C.

4. The method for producing a lithium secondary battery according to claim 1 , wherein the eutectic mixture contains lithium bis(fluorosulfonyl)imide (LiFSI) as a lithium salt.

5. 5. The method for producing a lithium secondary battery according to claim 4, wherein the eutectic mixture contains 0.5 to 1.5 moles of lithium bis(fluorosulfonyl)imide (LiFSI) per 1 L of succinonitrile.

6. 6. The method for producing a lithium secondary battery according to claim 1, wherein the eutectic mixture contains lithium bis(fluorosulfonyl)imide (LiFSI) and lithium difluoro(oxalate)borate (LiODFB) as lithium salts.

7. 7. The method for producing a lithium secondary battery according to claim 6, wherein the molar ratio of the lithium bis(fluorosulfonyl)imide (LiFSI) and the lithium difluoro(oxalate)borate (LiODFB) is 8:5 to 10:

3.

8. The method for producing a lithium secondary battery according to claim 1 , wherein the electrolyte further contains vinylene carbonate (VC) as an additive.

9. 9. The method for producing a lithium secondary battery according to claim 8, wherein the vinylene carbonate (VC) is contained in an amount of 1 to 5% by weight based on the total weight of the electrolyte solution.

10. The method for producing a lithium secondary battery according to claim 1 , wherein the electrolyte further contains fluoroethylene carbonate (FEC) as an additive.

11. The method for producing a lithium secondary battery according to claim 10, wherein the fluoroethylene carbonate (FEC) is contained in an amount of 3 to 15% by weight based on the total weight of the electrolyte solution.

12. The method for producing a lithium secondary battery according to claim 1 , wherein the activation step includes a step of charging for 4.5 hours to 7.5 hours.

13. The method for manufacturing a lithium secondary battery according to claim 1 , wherein the activation step is performed at a temperature of 40° C. to 50° C.

14. a positive electrode; a separator; a negative electrode; and an electrolyte; The electrolyte contains a eutectic mixture of succinonitrile and a lithium salt in an amount of 80% by weight or more based on the total weight of the electrolyte; the eutectic mixture contains lithium bis(fluorosulfonyl)imide (LiFSI) as a lithium salt; The eutectic mixture contains 0.5 to 1.5 moles of lithium bis(fluorosulfonyl)imide (LiFSI) per 1 L of succinonitrile; A lithium secondary battery having a discharge capacity retention rate of 80% or more after 79 cycles when repeatedly charged and discharged at a constant current of 0.1 C in the range of 2.5 V to 4.25 V.

15. 15. The lithium secondary battery according to claim 14, wherein the cell volume increase rate measured after storing the lithium secondary battery at 60° C. for two weeks is 10% or less.

Citation Information

Patent Citations

  • Plastic crystal electrolyte in lithium-based electrochemical device

    JP2013122921A

  • Eutectic liquid phase type secondary battery

    JP2017212174A

  • Electrolyte for lithium secondary battery and lithium secondary battery comprising the same

    KR1020190054920A